Report on the activities of the 46th Japanese Antarctic Research Expedition (JARE) wintering party, 2005-2006 - Kentaro Watanabe (National Institute of Polar Research, 2012)
The wintering party of the 46th Japanese Antarctic Research Expedition (JARE-46) was consisted of 37 expedition personnel. All members overwintered at Syowa Station. It conducted the fourth year's research and logistical program in the VIth five-year plan of JARE for one year from February 1, 2005 taking over management of the station from JARE-45 and all the members returned home safely on March 28, 2006. There were more bad weather days than usual but neither they nor the sea ice condition affected research activities. Planned data were collected steadily by routine and monitoring observations. Plans of research observations of the atmosphere, hydrosphere, geosphere and biosphere were implemented. For deep ice coring at Dome Fuji Station, fuel wastransported to the relay point and seven members participated in an inland joint party from October 17 to February 10. As the second year of a four-year plan of a clean-up project for Syowa Station, 18 used snow vehicles were recovered and a total of 205 tons of waste, more than targeted, was collected for removal from Antarctica. JARE-46 was involved actively in an outreach program with "Antarctic classes" held 45 times, connecting Syowa Station and schools or science museums in Japan and the U.S.A. through live images.